2012
DOI: 10.1155/2012/534512
|View full text |Cite
|
Sign up to set email alerts
|

Network Architecture, Security Issues, and Hardware Implementation of a Home Area Network for Smart Grid

Abstract: This paper discusses aims, architecture, and security issues of Smart Grid, taking care of the lesson learned at University of Pisa in research projects on smart energy and grid. A key element of Smart Grid is the energy home area network (HAN), for which an implementation is proposed, dealing with its security aspects and showing some solutions for realizing a wireless network based on ZigBee. Possible hardware-software architectures and implementations using COTS (Commercial Off The Shelf) components are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…PHEV can be recharged from an electrical power outlet. It has the potential to reduce Green House Gases (GHG) emissions and carbon footprint [38][39][40]. PHEV facilitates flexibility as well as economy in fuel usage [41][42][43].…”
Section: Application Of Wireless Sensor Network In Smart Gridmentioning
confidence: 99%
See 1 more Smart Citation
“…PHEV can be recharged from an electrical power outlet. It has the potential to reduce Green House Gases (GHG) emissions and carbon footprint [38][39][40]. PHEV facilitates flexibility as well as economy in fuel usage [41][42][43].…”
Section: Application Of Wireless Sensor Network In Smart Gridmentioning
confidence: 99%
“…It can be defined in various ways as per its functional, technological or beneficial aspects. As per the definition given by U.S. department of energy, "A smart grid uses digital technology to improve reliability, security, and efficiency (both economic and energy) of the electric system from large generation, through the delivery systems to from implementation of smart microgrid using personal area network based on IEEE 802.15.4 standard in University of Pisa in [39]. The relation between intricacy and security has been pointed out by Schumacher et al: "Complexity is the worst enemy of security" [40] (p. 531).…”
Section: Introductionmentioning
confidence: 99%
“…In our literature review we identified two major application areas related to energy efficiency: 1) Energy saving: Using sensors and actuators from Smart Home Environment for controlling energy savings by switching off or to low-power mode the consumer appliances currently not in use or according to the user preference settings. [8]. 2) Smart Grid: Integration that tends to the mix of vitality, mindful Smart Home Environment into the Smart Grid.…”
Section: B Energy Efficiencymentioning
confidence: 99%
“…Next, the organization and classification in four sections of main characteristics and requirements for HAN [4,41,50] is made, as shown in Figure 2. …”
Section: Smart Home Han Requirementsmentioning
confidence: 99%